A 3-year study of Candida infections among patients with malignancy: etiologic agents and antifungal susceptibility profile - Sharifi, Mahdieh; Badiee, Parisa; Abastabar, Mahdi; Morovati, Hamid; Haghani, Iman; Noorbakhsh, Mahta; Mohammadi, Rasoul (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Opportunistic fungal infections by Candida species arise among cancer patients due to the weakened immune system following extensive chemotherapy. Prophylaxis with antifungal agents have developed the resistance of Candida spp. to antifungals. Accurate identification of yeasts and susceptibility patterns are main concerns that can directly effect on the treatment of patients. Methods Over a period of three years, 325 cancer patients suspected to Candida infections were included in the current investigation. The clinical isolates were molecularly identified by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). All strains, were examined for in vitro susceptibility to the amphotericin B, itraconazole, fluconazole, and anidulafungin according to the CLSI M27 document. Results Seventy-four cancer patients had Candida infections (22.7%). Candida albicans was the most common species (83.8%). Antifungal susceptibility results indicated that 100% of the Candida isolates were sensitive to amphotericin B; however, 17.6%, 9.4%, and 5.4% of clinical isolates were resistant to anidulafungin, fluconazole, and itraconazole, respectively. Conclusion The findings of the present work shows a warning increase in resistance to echinocandins. Since all fluconazole resistance isolates were obtained from candidemia, we recommend amphotericin B as the first line therapy for this potentially fatal infection.